CARACTERÍSTICAS ESTRUTURAIS DE CULTIVARES DE AZEVÉM PERENE COMO CRITÉRIO DE SELEÇÃO PARA MAXIMIZAR O CONSUMO DE VACAS LEITEIRAS EM PASTEJO - Lesama, Manoel Flores (Scientia Agraria, 2003)
With the purpose to define criteria to select perennial ryegrass (Lolium perenne, L.) to improve its capacity to grazing, two experiments were conducted. The first experiment studied the effect of the grass structure against the production of milk comparing 4 diploid cultivars of late flowering perennial ryegrass under grazing. The swards were evaluated under rotational grazing using a total of forty-eight lactating dairy cows for three periods in the spring of 1999. They were offered 18 kg of dry matter (DM) to each cow daily. The differences in milk production were significant (P< 0.05) favoring the cultivar 3, with a result of 0.4 kg of milk per cow daily more than the 2 cultivar, considering the three periods. The digestibility and the nitrogen contents were similar between cultivars. The 2 cultivar showed higher tiller heights and bigger biomass with low tiller density and grazed volume, with reduced leaf lamina in the higher strata compared with the 3 cultivar. No significant difference among each cultivar intake has been established. The cows have compensated the low grazed volume in the 2 cultivar by increasing its grazing depth. They have ingested more pseudostems grazing the 2 cultivar compared to the other (14 cm vs. 8 cm during the second period considered). The intermediate sward strata included pseudostems with digestibility 6.7 points less than other strata and, in the 2 cultivar, the herbage eaten was probably less digestible than the others. The sward structure effects in milk production were measured more by the quality of selected herbage than its intake. Therefore, the sward structure has its effects in the interspecific performance. The morphological characters which determinate the sward structure can be used as a selection and evaluation criteria for improvement of cultivar. The second experiment tested the methodology proposed by Penning and Hooper (1985). The purpose was to know if the methodology is able to detect differences of ingestion short-term in very similar morphological structures and, in this way, assist in choosing of more grazing adapted cultivars selection criteria. It has been used 8 diploid perennial ryegrass cultivars with similar morphogenetical characteristics in a four-day evaluation. Each cultivar has been installed in 4 parcels, with 135 m2 per cultivar. Each plot (total of 32 plots) was grazed by four cows. The intake rate was verified by changing in weight pre and post grazing with metabolic weight loss correction. In each test day, four plots were used in the morning (plots A,B,C and O) and four in the afternoon (plots E, F, G and H). In those four days each cultivar had 2 parcels used by morning and 2 by afternoon. The intake rate has changed according with the daily period (morning/ afternoon), the days and the cultivars. The higher variation in the dry matter (DM) intake occurred into the day: 2.56 kg/hour DM in the morning to 3.07 kg/hour DM in the afternoon. The intake rate, when expressed by herbage fresh mass (FM) did not show a significant difference between periods: from 14.2 to 17.5 kg/ hour FM. Among the parameters which measure the sward characteristics only the DM contents has changed during the day: 18.6% to 24.6%. An increment in biomass, DM contents and sward surface height was encountered between days. Sward characteristics that had not changed between the days were the tiller density and the post graze height. 80th the DM and FM intake rate and the loss of weight increased significantly within the days of the experiment. With the exception of the DM intake, the FM intake did not interacted among the cultivars, grazing periods and/or days. Significant differences were noted among cultivars for biomass, height pre and post grazing, and with low correlation among them, tiller density but not for DM contents. Cultivars differences were not consistent with DM intake rate, the DM contents variations between daily periods could explain the cultivars effects inconsistency. The FM intake rate had the better adjustment to the sward characteristics, principally the lamina MS.